Regional disparities as a result of differences in human capital and innovativeness on the example of Poland - Jagódka, Maciej; Snarska, Małgorzata (Technological and Economic Development of Economy, 2023)
Inequalities in human capital most often affect other spheres of life. It is people who create innovation, so the unequal distribution of human capital and innovation in the regions leads to development disparities between regions. This, in turn, is a force inhibiting the achievement of higher levels of prosperity at the national level. The existing studies mainly focus on the assessment of disparities in development between countries. Although understandings of mechanisms of regional disparities, i.e., assessment of how and whether disparities are disappearing or widening under current socio-economic conditions is crucial to economic stability and cohesion, the problem of determinants of development and the pace of development between regions has rarely been studied in the economic literature. The purpose of the article, therefore, is to show how quickly weaker regions are catching up with more developed regions and that regional disparities are mainly the result of uneven human capital accumulation. The authors wonder if human capital in the regions is used similarly to create innovation. Hence, they examine the rate of development of these two relationships. The research: (1) determines the pace of development and adjustment processes by using the dynamic time warping method, (2) discovers if human capital is the main driver of regional disparities and is fully utilized in the creation of innovativeness. First published online 23 February 2023